2017
DOI: 10.1161/strokeaha.117.018380
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Smartphone Platform for Electronic Informed Consent in Acute Stroke Trials

Abstract: e-Consenting streamlined the consenting process in a randomized trial of patients with emergent large vessel occlusion strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 4 publications
1
42
0
Order By: Relevance
“…The e-Consent was then sent to the LAR’s smartphone for review. The e-Consent design has been previously published 4. In summary, we used REDCap (Research Electronic Data Capture), a secure Health Insurance Portability and Accountability Act-compliant web-based platform designed for research data capture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The e-Consent was then sent to the LAR’s smartphone for review. The e-Consent design has been previously published 4. In summary, we used REDCap (Research Electronic Data Capture), a secure Health Insurance Portability and Accountability Act-compliant web-based platform designed for research data capture.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported the pilot use of a smartphone platform for electronic informed consenting (e-Consent) in acute stroke trials 4. The e-Consent was found to streamline the consenting process in a RCT involving patients with emergent large vessel occlusion strokes (LVOS).…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests that telemedicine, which can include video conferencing, web-based materials, and other media, under certain circumstances, can provide care equal to that of in-person interactions, with potentially lower cost [30,31]. Additionally, early adopters of remote consent via multimedia platforms have found that utilization of such platforms can streamline the consent process, are appealing to prospective participants as users are more likely to opt for the remote option of consent (if available), and users have demonstrated equal satisfaction with in person vs remote consent options [32,33]. Toward this end, some STRIDE exemplar studies utilized eConsent with a remote consenting component.…”
Section: Remote Consenting and Telemedicinementioning
confidence: 99%
“…The wet signature is a feature in REDCap which allows participants to sign consent forms online in real time, by signing their name with their finger or computer mouse on a document as if the participant is using a pen and paper. 41 This process does not require an additional confirmation procedure 42 and is customary in REDCap consenting and data collection. 41 The informed consent document specifies the posting of clinical trial information at Clinical-Trials.…”
Section: Recruitment and Consentmentioning
confidence: 99%
“…41 This process does not require an additional confirmation procedure 42 and is customary in REDCap consenting and data collection. 41 The informed consent document specifies the posting of clinical trial information at Clinical-Trials. gov.…”
Section: Recruitment and Consentmentioning
confidence: 99%